Probiotic Bacillus subtilis QST713 improved growth performance and enhanced the intestinal health of yellow-feather broilers challenged with coccidia and Clostridium perfringens - Lu Sun; Yangbin Liu; Pan Xiao; Keying Zhang; Shiping Bai; Jianping Wang; Qiufeng Zeng; Huanwei Peng; Yadong Mu; Yue Xuan; Shanshan Li; Xuemei Ding (Poultry Science)
ABSTRACT: In this study, we investigated the effects of dietary supplementation with Bacillus subtilis (QST713) on the performance and intestinal health of yellow feather broilers under Coccidia and Clostridium perfringens (CP) challenge or CP alone. One-day-old yellow-feathered broiler roosters (n = 600) were randomly assigned to 5 groups (6 replicates with 20 roosters per replicate): the Con blank group, the CIC.p group (d24 Coccidia+d28-30 of CP challenge), the CIC.p + BS group (CIC.p +100 mg/kg B. subtilis), the C.p group (d 28–34 of CP challenge), and the C.p +BS group (C.p +100 mg/kg B. subtilis). The experiment lasted 80 d. The birds were evaluated for parameters such as average daily gain (ADG), average daily feed intake (ADFI), feed efficiency (F/G), intestinal lesion score, villus histomorphometry, intestinal tight junctions, inflammatory factors, and cecal microorganisms. The results revealed that 1) C.p. increased the F/G of broilers from 22 to 42 d (P < 0.05), whereas CIC.p. significantly decreased the 42 d and 80 d body weights (BW) and 22–42 d and 1–80 d ADG (P < 0.05) and significantly increased the 22 to 42 d and 1 to 80 d F/G (P < 0.05). The number of intestinal lesions significantly increased at 35 d and 42 d (P < 0.05). CIC.p significantly decreased the jejunum and ileum villus height (VH) and the ileum villus height/crypt depth (P < 0.05) at 35 d. The challenge significantly upregulated the expression of Claudin-1 and IL-4 mRNAs in the jejunum at 35 d and significantly downregulated the expression of IL-10 mRNA in the ileum at 35 d (P < 0.05); the number of unique OTUs in the challenge group decreased significantly after challenge treatment, and the relative abundances of Romboutsia at 35 d and Cladomyces and Lactobacillus at 42 d decreased significantly (P < 0.05). 2) Compared with the challenge groups, the addition of BS decreased the F/G of broilers from 22 to 42 d. Compared with the CIC group, the addition of BS significantly increased the F/G of broilers from 22 to 42 d. Compared with that in the CIC.p group, the addition of BS significantly increased the VH in the jejunum and ileum at 35 d (P < 0.05). Compared with the challenge groups, the BS groups presented significantly lower mRNA expression levels of Claudin-1 (P < 0.05) in the jejunum at 35 d. The Shannon and Chao indices suggested that BS increased the alpha diversity of cecum microorganisms in broilers. Dietary supplementation with B. subtilis can alleviate the damage to intestinal morphology and intestinal barrier function, as well as the altered cecal flora structure in broilers caused by Coccidia and C. perfringens infections.